RAGAM DAN METODE CORAK TAFSIR - Naili Sayyidatun Ni’mah; Muhammad Salman AlFarizi, Riska Amelia, Ana Rahmawati (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
This article discusses various methods and types of interpretation patterns used to study the interpretation of the Qur'an. This article examines traditional and modern interpretation methods, and their respective roles in understanding the text of the Koran. This article presents a qualitative study of translation methods and different styles in the study of text interpretation, using a literature review method. The main aim of this research is to examine and analyze various methods and types of interpretation that have developed in the study of texts, both in classical and modern times